Identifying the Risk and Protective Factors of Psychological Distress among Individuals in Asia during the COVID-19 Pandemic: A Systematic Literature Review - Ramadhanty, Amanda Meuthia; Tondok, Marselius Sampe (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
The COVID-19 pandemic has had a negative impact on individuals, such as psychological distress characterized by depression and anxiety. This research aims to determine the risk and protective factors that affect the psychological distress of individuals in Asia. This study used a systematic literature review method based on PRISMA (Preferred Reporting Items for Systematic and Meta-analysis). Articles were searched using specific keywords in the Google Scholar and Science Direct databases based on inclusion and exclusion criteria. Search articles using the keywords “psychological distress”, AND “COVID-19”, AND “individual psychological distress”, “COVID-19 Asia” on Google Scholar and ScienceDirect databases based on inclusion and exclusion criteria. The results of the synthesis of the 14 selected articles showed that there were risk factors and protective factors for psychological distress, which were grouped from sociodemographic factors, stress-related factors, internal factors, and external factors. Socio-demographic factors such as gender, age, marital status/ family status, and living in areas where the COVID-19 virus is spreading. Stress-related factors such as isolation, taking vitamins at home, and using social media to access negative news about the COVID-19 pandemic. Internal factors include congenital diseases and low self-efficacy. External factors include heavy workload, low income, lack of health protocols, less experienced in work, and just completed or graduated the education. The results of this study explain individual psychological distress, especially during a pandemic. Further research can conduct a meta-analysis to determine the effect size of risk and protective factors on psychological distress.